Kinase-deficient Pak1 mutants inhibit Ras transformation of Rat-1 fibroblasts. - Tang, Y (1997)
Among the mechanisms by which the Ras oncogene induces cellular transformation, Ras activates the mitogen-activated protein kinase (MAPK or ERK) cascade and a related cascade leading to activation of Jun kinase (JNK or SAPK). JNK is additionally regulated by the Ras-related G proteins Rac and Cdc42. Ras also regulates the actin cytoskeleton through an incompletely elucidated Rac-dependent mechanism. A candidate for the physiological effector for both JNK and actin regulation by Rac and Cdc42 is the serine/threonine kinase Pak (p65pak). We show here that expression of a catalytically inactive mutant Pak, Pak1(R299), inhibits Ras transformation of Rat-1 fibroblasts but not of NIH 3T3 cells. Typically, 90 to 95% fewer transformed colonies were observed in cotransfection assays with Rat-1 cells. Pak1(R299) did not inhibit transformation by the Raf oncogene, indicating that inhibition was specific for Ras. Furthermore, Rat-1 cell lines expressing Pak1(R299) were highly resistant to Ras transformation, while cells expressing wild-type Pak1 were efficiently transformed by Ras. Pak1(L83,L86,R299), a mutant that fails to bind either Rac or Cdc42, also inhibited Ras transformation. Rac and Ras activation of JNK was inhibited by Pak1(R299) but not by Pak1(L83,L86,R299). Ras activation of ERK was inhibited by both Pak1(R299) and Pak1(L83,L86,R299), while neither mutant inhibited Raf activation of ERK. These results suggest that Pak1 interacts with components essential for Ras transformation and that inhibition can be uncoupled from JNK but not ERK signaling.